2022
DOI: 10.1093/ofid/ofac105
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of High-Dose Cefazolin in Patients With High Body Weight: A Retrospective Cohort Study

Abstract: Background Cefazolin is a commonly used antibiotic for the treatment of mild to severe infections. Despite the use of higher dose of cefazolin (3 g/dose) for surgical prophylaxis in patients with obesity, there is currently a paucity of data identifying the optimal dose to treat infections in this specific patient population. Methods This was a multicenter, retrospective cohort study of patients who received cefazolin at weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In 2022, Ryu and colleagues evaluated the safety and effectiveness of higher cefazolin dosing (9 g/d) in patients weighing more than 120 kg with those given standard cefazolin dosing (6 g/d). 32 No significant differences in treatment-emergent adverse events (TEAEs) were identified between high-dose cefazolin in patients weighing more than 120 kg and standard-dose cefazolin regardless of body weight. Similarly, Simpson and colleagues presented data indicating no differences in TEAEs between those receiving cefazolin 2 g every 4 to 6 hours to traditional dosing of 1 to 2 g every 8 hours.…”
Section: Study Selection/data Extractionmentioning
confidence: 97%
“…In 2022, Ryu and colleagues evaluated the safety and effectiveness of higher cefazolin dosing (9 g/d) in patients weighing more than 120 kg with those given standard cefazolin dosing (6 g/d). 32 No significant differences in treatment-emergent adverse events (TEAEs) were identified between high-dose cefazolin in patients weighing more than 120 kg and standard-dose cefazolin regardless of body weight. Similarly, Simpson and colleagues presented data indicating no differences in TEAEs between those receiving cefazolin 2 g every 4 to 6 hours to traditional dosing of 1 to 2 g every 8 hours.…”
Section: Study Selection/data Extractionmentioning
confidence: 97%
“…Limited data are available on the safety and efficacy of cefazolin treatment dosing in obese patients. High‐dose cefazolin (up to 9 g/day) resulted in similar treatment outcomes and was well tolerated in the treatment of 33 patients weighing >120 kg versus 26 patients who received standard doses for the treatment of bacteremia or skin and soft tissue infection (SSTI) 6 …”
Section: Review Of Specific Antimicrobial Agentsmentioning
confidence: 99%
“…High-dose cefazolin (up to 9 g/ day) resulted in similar treatment outcomes and was well tolerated in the treatment of 33 patients weighing >120 kg versus 26 patients who received standard doses for the treatment of bacteremia or skin and soft tissue infection (SSTI). 6 Ceftriaxone Summary of previous recommendations. Not addressed in 2017 review due to lack of data.…”
Section: More Intensive Cefazolin Dosing Regimens Have Been Suggestedmentioning
confidence: 99%
“…Ryu and colleagues conducted a retrospective study in patients to evaluate the results and side effects between 2 groups of patients: those who received a high dosage of cefazolin that was dose-adjusted for body weight and those who received a conventional dose that was not weight-adjusted. In patients with high body weight, high-dose cefazolin was shown to be generally well tolerated, with no appreciable increase in side effects compared with the standard-dose group 28 . Salm and colleagues study’s conclusions showed that bodyweight-adjusted antimicrobial prophylaxis reduced the incidence of SSIs.…”
mentioning
confidence: 98%